Povos e comunidades tradicionais: das áreas protegidas à visibilidade política de grupos sociais portadores de identidade étnica e coletiva¹ - Calegare, Marcelo Gustavo Aguilar; Higuchi, Maria Inês Gasparetto; Bruno, Ana Carla dos Santos (Ambiente & Sociedade, 2014)
The main goal of this article is to review schematically the three vectors that influenced the consolidation of the labeling "traditional peoples and communities" in Brazil, highlighting the Amazon cases. These are: a) the international environmentalism discussions; b) the development of the debate at the national level; c) the appropriation by social groups labeled as such. The focus is to show that with the Decree nº 6040/07 the term itself has transformed and no longer is restricted to the Protected Areas. It came to designate self-defined social groups by different collective identities, who struggle for basic social rights and territory, access to natural resources and recognition in public policy that suit their needs.
Traditional peoples and communities: from protected areas to the political visibility of social groups having ethnical and collective identity
Keywords: Indigenous Peoples; Amazon; Protected Areas; Traditionally Occupied Land; Collective Identity; Povos E Comunidades Tradicionais; Amazônia; Areas Protegidas; Território Tradicionalmente Ocupado; Identidade Coletiva